PENGARUH PERILAKU ORGANISASI TERHADAP PENINGKATAN PRODUKTIVITAS KERJA PEGAWAI DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN SIDENRENG RAPPANG - Sri Ramadani Nurul Fitri; Saifullah Saifullah (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
The purpose of this study was to determine the effect of organizational behavior on improving employee productivity at the Library and Archives Service of Sidenreng Rappang Regency. The population of this study were 41 people in the Office of Library and Archives of Sidenreng Rappang Regency aged 17 years and over. The sample in this study were 39 employees in the Department of Library and Archives, based on the sampling technique saturated with this type of research is descriptive quantitative. Sources of data in this study are primary data and secondary data. Data collection techniques used in this study were observation, questionnaires, interviews and documentation. The results of the influence of organizational behavior on the increase in work productivity of employees at the Office of Library and Archives of Sidenreng Rappang Regency, it turns out that the value of t count ≥ t table or 4.493 ≥ 2.026, and a significant level of 0.000. then H0 is rejected and Ha is accepted, meaning that it has a significant effect on increasing work productivity (Y). Y) with a yield of 39.8%. While the remaining 100% - 39.8% = 60.2% (influenced by other factors) which are not included in this study. So that 39.8% is still classified as low organizational behavior towards increasing the work productivity of employees at the Library and Archives Office of Sidenteng Rappang Regency.